Prevalence of Venous Thromboembolism in Critically Ill COVID-19 Patients: Systematic Review and Meta-Analysis - Mohamed, Mouhand F. H.; Al-Shokri, Shaikha D.; Shunnar, Khaled M.; Mohamed, Sara F.; Najim, Mostafa S.; Ibrahim, Shahd I.; Elewa, Hazem; Abdalla, Lina O.; El-Bardissy, Ahmed; Elshafei, Mohamed Nabil; Abubeker, Ibrahim Y.; Danjuma, Mohammed; et al. (Frontiers in Cardiovascular Medicine, 2021)
Background: Recent studies revealed a high prevalence of venous thromboembolism (VTE) events in coronavirus disease 2019 (COVID-19) patients, especially in those who are critically ill. Available studies report varying prevalence rates. Hence, the exact prevalence remains uncertain. Moreover, there is an ongoing debate regarding the appropriate dosage of thromboprophylaxis. Methods: We performed a systematic review and proportion meta-analysis following PRISMA guidelines. We searched PubMed and EMBASE for studies exploring the prevalence of VTE in critically ill COVID-19 patients till 22/07/2020. We pooled the proportion of VTE. Additionally, in a subgroup analysis, we pooled VTE events detected by systematic screening. Finally, in an exploratory analysis, we compared the odds of VTE in patients on prophylactic compared to therapeutic anticoagulation. Results: The review comprised of 24 studies and over 2500 patients. The pooled proportion of VTE prevalence was 0.31 (95% CI 0.24, 0.39 I2 94%), of VTE utilizing systematic screening was 0.48 (95% CI 0.33, 0.63 I2 91%), of deep-venous-thrombosis was 0.23 (95% CI 0.14, 0.32 I2 96%), of pulmonary embolism was 0.14 (95% CI 0.09, 0.20 I2 90%). Exploratory analysis of few studies, utilizing systematic screening, VTE risk increased significantly with prophylactic, compared to therapeutic anticoagulation (OR 5.45; 95% CI 1.90, 15.57 I2 0%). Discussion: Our review revealed a high prevalence of VTE in critically ill COVID-19 patients. Almost 50% of patients had VTE detected by systematic screening. Higher thromboprophylaxis dosages may reduce VTE burden in this patient's cohort compared to standard prophylactic anticoagulation; however, this is to be ascertained by ongoing randomized controlled trials.